Escaping the exception: Migrant sex workers between subjectification and excess - Peano, Irene (The Greek Review of Social Research, 2013)
The paper examines the play of multiple, displacing and emplacing regimes of subjectification as they impinge upon the life experiences of migrant Nigerian sex workers, as well as the ways in which the women’s subjectivities might exceed such regimes. Dispositifs such as those of migration policy and humanitarianism, of precariousness and institutionalised predation in neoliberal economies, but alsoof gender and kinship, interweave through complex genealogies that do not yield unequivocal victim-subjects or, on the contrary, subjects enforcing exploitation from a position of power. Likewise, neither mobility nor stasis, or border crossings and settled lives are straightforwardly mappable on excess or constraint: migration and return are experienced ambiguously, alternatively as liberating and constraining.